Navigating Workforce Diversity in Organizational Development and Employee Satisfaction in the Automobile Sector (Journal of Informatics Education and Research, 2024)
This study examines the effects of the processes of organizational development for the satisfaction of employees in the automobile sector in the Marathwada area. Given the emphasis on the differences of these practices for demographic characteristics, the research employed a mixed-methods approach and used quantitative surveys with 423 workers from different organisations. Major findings identified a strong positive relationship between training and development and other effective practices and employee satisfaction. However, the majority of the young employees answered with higher levels of satisfaction, underlining the need to cater for different and developing employee segments. Consequently, the analysis suggests that organizations who place emphasis on these development practices will improve employees’ morale and retention. From this case, it is evident that Human Resources Managers should pursue strategic HRM to establish workplace productivity and enduring organizational development. Recognising the needs of many different groups in society allows for better more efficient organisational development by companies.